Treating wartime injuries amidst attack: insights from a medical facility on the edge of combat - Chezy Levy; Gili Givaty; Yaniv S. Ovadia; Mor Saban (Conflict and Health, 2024)
Abstract Background Providing emergency care during conflict poses unique challenges for frontline hospitals. Barzilai Medical Center (BUMCA) in Ashkelon, Israel is a Level I trauma center located close to the Gaza border. During the November 2023 escalation of conflict, BUMCA experienced surging numbers of civilian and military trauma patients while also coming under rocket fire. Methods We conducted a retrospective review of BUMCA operational records and 827 de-identified patient records from October 7–14, 2023. Records provided data on daily patient volumes, injury patterns, resource constraints, and impacts of rocket attacks on hospital function. Basic demographic data was obtained including age, gender, injury severity scores, and disposition. Results Of the 827 patients brought to BUMCA, most (n = 812, 98.2%) presented through the emergency department. Tragically, 99 individuals were pronounced dead on arrival. Injury severity assessments found nearly half (47%) had minor injuries such as lacerations, contusions and sprains, while 25% exhibited moderate injuries like deep lacerations and fractures. 15% sustained severe or critical injuries including severe head injuries. The largest age group consisted of adults aged 19–60 years. No pediatric patients were admitted despite proximity to residential neighborhoods. The majority of cases (61%) involved complex polytrauma affecting multiple body regions. BUMCA served as both the primary treatment facility and a triage hub, coordinating secondary transports to other trauma centers as needed. Patient volumes fluctuated unpredictably from 30 to an overwhelming 125 daily, straining emergency services. Resources faced shortages of beds, medical staff, supplies and disruptions to power from nearby missile impacts further challenging care delivery. Conclusion Despite facing surging demand, unpredictable conditions and external threats, BUMCA demonstrated resilience in maintaining emergency trauma services through an adaptive triage approach and rapid surges in capacity. Their experience provides insights for improving frontline hospital preparedness and continuity of care during conflict through advance contingency planning and surge protocols. Analysis of patient outcomes found a mortality rate of 15% given the complex, multi-region injuries sustained by many patients. This study highlights the challenges faced and strengths exhibited by medical professionals operating under hazardous conditions in minimizing loss of life. Patient and public involvement in research Given that the study analyzed patient data from a hospital treating casualties of an ongoing armed conflict, directly engaging patients or the public during the sensitive research process could have posed risks. The volatile security situation and restrictions and protections in place amidst the crisis made it not feasible or appropriate to involve them in the study’s design, methods, reporting of results, or dissemination plans. Our aim was to conduct this retrospective analysis in a way that did not endanger those affected or compromise the hospital’s emergency response operations.